Pengaruh Stock Buyback Terhadap Kinerja Saham dan Kinerja Keuangan Studi Kasus pada PT. Jasuindo Tiga Perkasa, Tbk - Bintang Sahala Marpaung; Adil Fadillah (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2012)
Stock buyback is repurchasing of shares from public by the company (the issuer). This corporate action is usually held if the company has surplus of retained earnings, but has little opportunity to invest, or it could be held when the company’s stock price declined. But quite a lot of companies that do stock buyback even though its stock price has not decreased. The goal is not only to increase the stock price return, but also to pursue the stability of price in the stock market and convince people that the condition of the issuer or the investor is still quite strong. Stock buyback programs are also part of the investment strategy in order to increase the value of the company. This study aims to determine the effect of stock buyback on a company’s financial performance (as measured using EPS indicator) and the company’s stock performance (as reflected in stock market prices and PER). The company researched was PT Jasuindo Tiga Perkasa, Tbk., which did buyback in the period of October 22, 2008 – January 31, 2009. The period of the sudies are 7 quarters before buyback, 2 quarters of buyback execution, and 7 quarters after after buyback. The results suggest that the company’s reason to do buyback is because stock prices are likely to be low, below the theretical price. Besides that buyback activity is funded by the company’s retained earnings because at the period before the buyback, the value of the company’s net income tends to increase. After the company’s buyback, then the company’s financial performance is likely to increase; this is evidenced by the value of one quarter of EPS subsequent to the second session buyback appears to increase up to 150%. But the increase in EPS is not matched by an increase in stock performance. This is evidenced by the stock price tends to flat during four quarters and PER value which tend to decrease. Based on the research results, the conclusion is the improved financial performance that is not offset by an increase of stock performance is caused by market expectations which tend to assume that business firms will not be positive in the future. This is due to the company provided less information to the public (society)